Effect of adipokine and ghrelin levels on BMD and fracture risk: an updated systematic review and meta-analysis - Lee, Seoyul; Kim, Jeong Hun; Jeon, Yun Kyung; Lee, Jung Sub; Kim, Keunyoung; Hwang, Sun-Kyung; Kim, Jae Ho; Goh, Tae Sik; Kim, Yun Hak (Frontiers in Endocrinology, 2023)
Context: Circulating adipokines and ghrelin affect bone remodeling by regulating the activation and differentiation of osteoblasts and osteoclasts. Although the correlation between adipokines, ghrelin, and bone mineral density (BMD) has been studied over the decades, its correlations are still controversial. Accordingly, an updated meta-analysis with new findings is needed. Objective: This study aimed to explore the impact of serum adipokine and ghrelin levels on BMD and osteoporotic fractures through a meta-analysis. Data Sources: Studies published till October 2020 in Medline, Embase, and the Cochrane Library were reviewed. Study Selection: We included studies that measured at least one serum adipokine level and BMD or fracture risk in healthy individuals. We excluded studies with one or more of the following: patients less than 18 years old, patients with comorbidities, who had undergone metabolic treatment, obese patients, patients with high physical activities, and a study that did not distinguish sex or menopausal status. Data Extraction: We extracted the data that include the correlation coefficient between adipokines (leptin, adiponectin, and resistin) and ghrelin and BMD, fracture risk by osteoporotic status from eligible studies. Data Synthesis: A meta-analysis of the pooled correlations between adipokines and BMD was performed, demonstrating that the correlation between leptin and BMD was prominent in postmenopausal women. In most cases, adiponectin levels were inversely correlated with BMD. A meta-analysis was conducted by pooling the mean differences in adipokine levels according to the osteoporotic status. In postmenopausal women, significantly lower leptin (SMD = -0.88) and higher adiponectin (SMD = 0.94) levels were seen in the osteoporosis group than in the control group. By predicting fracture risk, higher leptin levels were associated with lower fracture risk (HR = 0.68), whereas higher adiponectin levels were associated with an increased fracture risk in men (HR = 1.94) and incident vertebral fracture in postmenopausal women (HR = 1.18). Conclusions: Serum adipokines levels can utilize to predict osteoporotic status and fracture risk of patients.